Development and pilot studies of the features of a diamond drill crown operation when drilling in solid anisotropic rocks - Vyacheslav Neskoromnykh; Pavel Petenev; Alexander Neverov; Pavel Pushmin; Grigory Romanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Relevance of work is caused by need of a solution of the problem of increase of efficiency of drilling of deep wells for solid anisotropic rocks. Work purpose: Research and development of new model of a diamond drill bit for drilling of solid anisotropic rocks. Research methods: Analytical researches and experimental works new diamond crown at the boring stand. Results: The model of the new diamond crown allowing to realize drilling of anisotropic rocks is developed. Data of the analytical analysis and technique of experimental works at the boring stand are submitted. Skilled drilling is carried out by a new crown which showed features of mechanics of work of a skilled crown that allows to carry out improvement of a design of the boring tool. Are determined consistent patterns of influence of parameters of the mode of drilling on character and intensity of wear of a crown, mechanical speed of drilling, power consumption of process of drilling. Conclusions. The skilled crown developed for conditions of drilling of wells in solid anisotropic rocks in the conditions of experimental drilling showed the high performance. The received results of experimental works confirmed the analysis and allowed to specify the mechanism of work of a skilled crown at various parameters of the mode of drilling with application as the clearing agent as waters, and emulsions. New data on the mechanism of work of a crown will be used for a crown prototype design creation of the perfect that will allow to receive more perfect boring instrument for drilling of solid anisotropic rocks.